Effect of Er: YAG Laser Pulse Width on Shear Bond Strength Between Layered Ceramic and Zirconia Substructure: Er: YAG pulse width and ceramic-zirconia bond strength - BoroujerdiKarimi , Pouria; Ebrahim, Negar; Chiniforush, Nasim; Masaeli, Reza; Allahyari, Somayeh (Journal of Lasers in Medical Sciences, 2025)
Introduction: This study aimed to investigate the influence of different erbium-doped yttrium aluminum garnet (Er: YAG) laser pulse widths (pulse durations) on the shear bond strength (SBS) of layered ceramic to zirconia substructures. Methods: A total of 60 zirconia blocks (5 mm radius and 10 mm height) were divided into 6 groups. Group C received no treatment, while Group S was treated with sandblasting using aluminum oxide (Al2O3). Groups L1, L2, L3, and L4 were irradiated with Er: YAG lasers with pulse widths of 50 µs, 100 µs, 300 µs, and 600 µs, respectively. The layered ceramics were applied using a custom index and then sintered. The specimens were mounted in acrylic resin and subjected to a SBS test at a speed of 0.5 mm/min using a universal testing machine until the bonding surface developed cracks. The mode of failure was observed under a microscope. Results: The highest SBS was observed in the L4 and L2 groups, followed by the L3, L1, and S groups. Group C showed the least SBS. However, no significant difference was found between laser groups (L1, L2, L3, and L4) and group S. Conclusion: In conclusion, this study highlights the importance of surface treatment in improving the bond strength of zirconia restorations. The use of Er: YAG laser irradiation can produce a rougher surface, which is beneficial for adhesion. These findings provide valuable insights for clinicians seeking to improve the durability and longevity of zirconia-based restorations.